Perspectives in business informatics research : 18th International Conference, BIR 2019, Katowice, Poland, September 23-25, 2019, proceedings /: 18th International Conference, BIR 2019, Katowice, Poland, September 23-25, 2019, proceedings. ([2019]) - Unknown
No abstract available